2016
DOI: 10.1021/acs.jproteome.6b00430
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Analysis of Hormone-Responsive and Triple-Negative Breast Cancer Cell Responses to Paclitaxel Identify Key Metabolic Differences

Abstract: To date, no targeted therapies are available to treat triple negative breast cancer (TNBC), while other breast cancer subtypes are responsive to current therapeutic treatment. Metabolomics was conducted to reveal differences in two hormone receptor-negative TNBC cell lines and two hormone receptor-positive Luminal A cell lines. Studies were conducted in the presence and absence of paclitaxel (Taxol®). TNBC cell lines had higher levels of amino acids, branched-chain amino acids, nucleotides and nucleotide sugar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 113 publications
2
38
0
1
Order By: Relevance
“…Our KEGG pathway computational analysis revealed that miR-95 is involved in different cellular processes, including lysine degradation. This is in agreement with a previous study that demonstrated that lysine is a metabolite that distinguishes TNBC cells from hormone-positive breast cancer cells (72). Given that the amino acid metabolism is a major source of energy and carbon for tumor cell growth and survival (73), the dysregulation of the lysine degradation pathway may result from changes in the energy metabolism of tumor cells.…”
Section: Discussionsupporting
confidence: 92%
“…Our KEGG pathway computational analysis revealed that miR-95 is involved in different cellular processes, including lysine degradation. This is in agreement with a previous study that demonstrated that lysine is a metabolite that distinguishes TNBC cells from hormone-positive breast cancer cells (72). Given that the amino acid metabolism is a major source of energy and carbon for tumor cell growth and survival (73), the dysregulation of the lysine degradation pathway may result from changes in the energy metabolism of tumor cells.…”
Section: Discussionsupporting
confidence: 92%
“…In a previous study [ 26 ], we compared the metabolic and inflammatory responses of these hormone receptor-positive (Luminal A) and TNBC cell lines following treatment with the widely used chemotherapeutic paclitaxel (Taxol®). There, we showed differences between both the cells classified by the same subtype (BT474 versus MCF-7 and MDA-MB-231 versus MDA-MB-468) and between the two subtype cell models (Luminal A versus TNBC) [ 26 ]. Based on our findings, we felt further investigation of the metabolic differences was warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that 1 and 3nM PTX had an impact on morphology and viability of cancer cells. 10,19 Therefore, we investigated whether PTX at concentration (1-3 nM) had similar effects in mtp53 HPSCC. The results showed that PTX at a concentration (1-3 nM) did not inhibit cell growth ( Figure 1B).…”
Section: Low Concentration Ptx Did Not Affect Cell Viability Of Mtp53mentioning
confidence: 99%